Chitosan-Grafted Copolymers and Chitosan-Ligand Conjugates as Matrices for Pulmonary Drug Delivery. (4th October 2011) - Andrade, Fernanda; Goycoolea, Francisco; Chiappetta, Diego A.; das Neves, José; Sosnik, Alejandro; Sarmento, Bruno
Abstract : Recently, much attention has been given to pulmonary drug delivery by means of nanosized systems to treat both local and systemic diseases. Among the different materials used for the production of nanocarriers, chitosan enjoys high popularity due to its inherent characteristics such as biocompatibility, biodegradability, and mucoadhesion, among others. Through the modification of chitosan chemical structure, either by the addition of new chemical groups or by the functionalization with ligands, it is possible to obtain derivatives with advantageous and specific characteristics for pulmonary administration. In this paper, we discuss the advantages of using chitosan for nanotechnology-based pulmonary delivery of drugs and summarize the most recent and promising modifications performed to the chitosan molecule in order to improve its characteristics.